Multiple Introduction and High Genetic Diversity: Drivers for Successful Establishment of Invasive Peacock Bass (Cichla spp.) in Peninsular Malaysia - Khaleel, Aliyu Garba; Mohd Nasir, Muhammad Syafiq Aiman; Mohd Dali, Mohamad Zulkarnain; Madiran, Norainsyafikah; Md Sheriff, Shahreza; Seong Wei, Lee; Hou Chew, Ha; Ismail, Norshida; Kamarudin, Ahmad Syazni (Trends in Sciences, 2023)
The introduction of invasive Cichla spp. was followed by the several reports regarding the decline of local freshwater native species in Malaysia. The purpose of this research was to generate information concerning the introduction history of Cichla spp. in Malaysia. Studies on genetic diversity and structure provides the essential baseline data for monitoring and conservation of invasive species. This will help to clearly understand the propagule pressure and genetic distribution of Cichla spp. in the invaded freshwaters of Malaysia. A total of 61 samples of Cichla spp. were collected from 9 sampling location in Malaysia for mitochondrial DNA (control region) analysis. Overall samples showed high genetic diversity (Hd, 0.6700; π, 0.0254) and yielded 9 haplotypes resulted from different Cichla spp. present. The maximum likelihood tree with strong bootstrap support revealed that Cichla spp. forms 3 clusters, and confirmed to be C. monocoulus, C. occelaris and C. temensis. Except for Malacca populations, other populations were largely dominated by either C. monocoulus or C. occelaris. The current study suggesting that more than one introduction event of invasive Cichla spp. occurred in Malaysia. HIGHLIGHTS One of the common problem in the conservation effort for Malaysia’s freshwater aquatic ecosystem is failure to understand the introduction events of invasive species (Cichla) Mitochondrial DNA analysis (control region) conducted in order to find the genetic diversity and genetic structure of invasive Cichla across freshwater habitats in Malaysia High genetic diversity was observed, suggesting multiple introduction occurance of invasive Cichla in the country GRAPHICAL ABSTRACT